Kratopenia as an indicator of sarcopenia in smokers: Cut-off points for peak knee torque. - Paolla Sanches; Karina A de S Souza; Alexandre R P Ambrozin; André R Pereira; Leandro L da Silva; Amanda S Cano; Luciana Pinato; Tiago V Barreira; Dionei Ramos; Mahara Proença (PLOS Global Public Health)
Muscle strength is a crucial predictor of adverse outcomes and is essential for identifying kratopenia and physical limitations. Smoking can aggravate this condition, damaging the musculoskeletal system. Assessing muscle strength, especially with portable dynamometers, is essential for early detection of muscle dysfunction. Studies demonstrate the importance of standardizing protocols and defining cut-off points for peripheral muscle weakness in general. Thus, focusing on the effects of smoking on muscle function, the objective was to investigate cut-off points based on functional limitation and identify the presence of kratopenia in smokers. This cross-sectional study, composed of smokers (conventional cigarettes), regardless of gender, aged over 18 years, was conducted with a comprehensive approach. The volunteers were evaluated by personal data, carbon monoxide analysis (monoximetry), and physical-functional aspects such as lung function (spirometry), functional performance (6-minute walk test, sit-to-stand, fourmeter gate speed, and physical activity in daily life), and peripheral muscle strength (portable digital dynamometry). A total of 143 smokers were evaluated, with high levels of tobacco dependence and preserved lung function. Men showed significantly higher peripheral muscle strength across all variables (p < 0.05). ROC analysis revealed acceptable discrimination for detecting kratopenia from functional limitation: AUC of 70% for knee extension (p < 0.01) from the cut-off points identified for knee extension lower than 214.8Nw and 273.6Nw; and 70% for knee flexion (p < 0.01) lower than 125 Nw and 156.2Nw, women and men, respectively, to be loss of muscle strength and power. Kratopenia was present in > 50% of participants based on peak torque (Nw) (56% of knee extension and 52% of knee flexion), being more prevalent in women. Peak knee torque measurements, especially those of extension and flexion, can determine kratopenia in limited functional smokers. Determining specific cut-off points offers an effective tool to identify and prevent sarcopenia risk in smokers.